A systematic review of complications in prepectoral breast reconstruction. Issue 7 (July 2019) - Wagner, Ryan D.; Braun, Tara L.; Zhu, Huirong; Winocour, Sebastian
Summary: The use of implants for breast reconstruction began over four decades ago, with implants initially placed in the prepectoral space. Concerns arose regarding the high incidence of capsular contracture and complication rates. With the introduction of acellular dermal matrix (ADM), plastic surgeons are again considering the advantages of prepectoral implant placement. A systematic review was conducted to examine complication profiles in prepectoral breast reconstruction alone versus prepectoral with ADM or mesh. A systematic review of the PubMed database was performed from inception to March 2017 to identify literature on postmastectomy patients undergoing prepectoral breast reconstruction with and without ADM or mesh. Study characteristics, complication rates, and outcomes were extracted for analysis. Study quality was assessed using the Newcastle–Ottawa Scale, and complication profiles were analyzed using the random-effects model. Twenty-seven studies met criteria for inclusion out of 550 identified for review. For 1881 total breasts, the complication rate with ADM was 23.4%, while the rate without an additional implant material was 27.5%. The difference in the capsular contracture rate with and without ADM was 2.3% and 12.4%, respectively. The use of ADM in prepectoral breast reconstruction correlated with lower capsular contracture and overall complications rates; however, rates of implant loss, infection, and mastectomy flap necrosis were higher with the use of ADM. Results were variable across studies, and in general, the quality of evidence reported was low. Because the methodology for outcome assessment was inconsistent, there is a need for further investigation with comparative studies and standardized outcome reporting.